Model Improvement of Students’ Entrepreneurial Intentions in SMP Satu Atap Kandangserang - Setiawan, Umam Aries; Yanto, Heri; Prihandono, Dorojatun (Journal of Economic Education, 2021)
The aim of this study is to determine the influence of society, school environment, the role of parents, friend circle, and self-efficacy on students' intentions to be an entrepreneur. The population of this study was the 9th grade students of SMP Satu Atap Kandangserang in the academic year of 2020/2021. There were 117 students as the sample of the study who were taken using proportional random sampling technique. The data collection technique used was a linkert scale questionnaire, which was given directly to the respondent. The data analysis used the IBM SPSS 24 and AMOS 20 path analysis. The results showed that the influence of society, parents, school, friend circle on self efficacy also the influence of society on entrepreneurial intention have a significant effect. While the influence of parents, school on entrepreneurial intention have no significant effect. Furthermore, the influence of self efficacy on entrepreneurial intention has a significant effect, the goodness fit test showed that the significance probability of all variables can be accepted.